2022
DOI: 10.1021/acs.jpca.2c03059
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Interfacial and Bulk Kinetics Govern the Timescales of Multiphase Ozonolysis Reactions

Abstract: Chemical transformations in aerosols impact the lifetime of particle phase species, the fate of atmospheric pollutants, and both climate- and health-relevant aerosol properties. Timescales for multiphase reactions of ozone in atmospheric aqueous phases are governed by coupled kinetic processes between the gas phase, the particle interface, and its bulk, which respond dynamically to reactive consumption of O3. However, models of atmospheric aerosol reactivity often do not account for the coupled nature of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(95 citation statements)
references
References 113 publications
4
91
0
Order By: Relevance
“…smaller, and such difference may also imply that the effective ionic strength at the interface layers where the surface reactions occurs is smaller than that in the aerosol bulks. Indeed, the fitted values of partial coverage θ ss suggest that the surface STS concentration remains around 1.3 × 10 14 cm −2 (or around 2.5 M), such as [STS] ss,0 plotted in Figure 7, when the bulk STS concentration is larger than ∼4 M. Such kind of dependence has also been found in the cases of nitrites and nitrates, and it was rationalized in terms of Langmuir adsorption model, 39 where the surface sites for these ions are also limited, leading to a constant plateau of surface concentrations at higher bulk concentrations. However, it should note that θ ss employed in the present work is assumed to be independent of time, and thus in principle it takes into account the surface depletions of all ions (Na + , S 2 O 2-3 , SO 2-4 and HSO -4 ) appeared at different reaction time scales.…”
Section: Interfacial Depletion Of Ionssupporting
confidence: 53%
See 1 more Smart Citation
“…smaller, and such difference may also imply that the effective ionic strength at the interface layers where the surface reactions occurs is smaller than that in the aerosol bulks. Indeed, the fitted values of partial coverage θ ss suggest that the surface STS concentration remains around 1.3 × 10 14 cm −2 (or around 2.5 M), such as [STS] ss,0 plotted in Figure 7, when the bulk STS concentration is larger than ∼4 M. Such kind of dependence has also been found in the cases of nitrites and nitrates, and it was rationalized in terms of Langmuir adsorption model, 39 where the surface sites for these ions are also limited, leading to a constant plateau of surface concentrations at higher bulk concentrations. However, it should note that θ ss employed in the present work is assumed to be independent of time, and thus in principle it takes into account the surface depletions of all ions (Na + , S 2 O 2-3 , SO 2-4 and HSO -4 ) appeared at different reaction time scales.…”
Section: Interfacial Depletion Of Ionssupporting
confidence: 53%
“…[35][36][37][38] A very recent kinetics study of nitrite ozonolysis in aerosols investigated the significant dependence of interfacial nitrite concentrations on bulk nitrite concentrations and its potential role in the interfacial kinetics. 39 The pH at surfaces of aerosols can also be different from those in aerosol bulks, 40 and a recent aerosol kinetics study observed the enhanced rates of catalyzed oxidations in aerosols and attributed this enhancement to the pH gradient at the air-water interfaces of aerosols. 41 In the present work, we choose the oxidation reaction of sodium thiosulfate (STS), Na 2 S 2 O 3 , with O 3 as a model system of sulfur oxidation in aerosols, as such model reaction has been utilized in several studies associated with atmospheric aerosol chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This framework does not resolve the formation of chemical gradients that might emerge in either the interfacial or bulk volumes, but instead considers [X] and [Y] in each region as average quantities. For the derivations presented below, the same view of the interface and bulk regions of the droplet is used, which although simplistic in molecular terms, appears to be realistic enough to correctly predict the experimentally measured kinetics and reactive uptake coefficients observed during multiphase ozonolysis.…”
Section: Methodsmentioning
confidence: 99%
“…H cc gs can be expressed kinetically using the rate constants for the forward adsorption and backward desorption elementary steps (Figure ), where A is surface area, c̅ is the mean speed of X (g) and σ is the sticking probability per adsorption site, with the assumption that each X (g) may occupy a single site to become X (ads) . H cc sb can be similarly expressed using the rate constants for the forward solvation and backward desolvation elementary steps illustrated in Figure , Γ ∞( X ) is the maximum surface concentration (molec cm –2 ) of X and δ is the interfacial thickness. We assume an interfacial thickness of 1 nm, which is consistent with the estimated solvation energy profile for trace gas adsorption in MD simulations. , δ is used to compute volumetric surface concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation